Strategi Memadukan Pembelajaran Bahasa Arab dan Pendidikan Islam Moderat di Pesantren Al- Ma’arif - Muhammad Said; Muhammad Makinuddin; Hani’atul Khoiroh (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to examine and formulate integrative strategies for combining Arabic language instruction with moderate Islamic education in Islamic boarding schools as a means of cultivating students who are both linguistically proficient and characterized by wasathiyah (moderation). Employing a descriptive qualitative approach with a field research design, the study was conducted at Al-Ma’arif Islamic Boarding School in Jombang, East Java. Data were collected through participatory observation, semi-structured in-depth interviews, and document analysis involving 20 respondents, including Arabic language teachers, students, and institutional leaders. The data were analyzed using the interactive model of Miles and Huberman, with validity ensured through triangulation and member checking. The findings reveal that the integration of Arabic learning and moderate Islamic education is implemented systemically through four interrelated components: curriculum integration, contextual-reflective instructional methods, the reinforcement of a moderate language environment (bi’ah lughawiyyah), and holistic evaluation encompassing cognitive, affective, and social dimensions. Empirical evidence indicates that this integrative strategy not only enhances students’ Arabic language competencies but also effectively internalizes values of Islamic moderation such as tolerance, justice, and balance thereby positioning Arabic as both an academic and moral-ideological instrument in fostering inclusive, critical, and peace oriented student character.